Plasma irisin and the brain-derived neurotrophic factor levels in sedentary subjects: effect of 8-weeks lifestyle intervention - Radikova Zofia; Mosna Lucia; Eckerstorfer Carmen; Bajer Boris; Havranova Andrea; Imrich Richard; Vlcek Miroslav; Penesova Adela (Endocrine Regulations)
Objectives. Sedentary lifestyle increasingly observed in the population contributes to the incremental incidence of obesity, cardiovascular diseases, mental disorders, type 2 diabetes, hyper-tension, dyslipidemia, and others. Physical inactivity together with an imbalance in caloric intake and expenditure leads to a loss of muscle mass, reduced insulin sensitivity, and accumulation of the visceral fat. Organokines (adipokines, myokines, hepatokines, etc.) serve in the organism for inter-organ communication. However, human studies focused on the exercise-related changes in plasma levels of certain myokines have produced contradictory results. In the present study, we verified a hypothesis that myokine irisin, which is expected to increase in response to physical activity, induces brain-derived neurotrophic factor (BDNF) production and by this way mediates the beneficial effect of exercise on several brain functions.